Costa Rica - Recapturing Momentum for Poverty Reduction - Mason, Andrew D.; Sobrado, Carlos (World Bank, Washington, DC, 2012)
Costa Rica is well-known for its socio-economic achievements with low levels of poverty and inequality by Latin American standards. It also performs well in health, access to improved water supplies, suitable housing and other basic services, including electricity and sanitation, relative to comparable countries. Nonetheless, the country faces important challenges in the on-going fight against poverty.